High-resolution two-photon fluorescence microscope imaging of nanodiamonds containing NV color centers - Zhiping Ju; Mengting He; Junjie Lin; Jing Zhu; Botao Wu; E Wu (Results in Physics, 2022)
Fluorescent nanodiamonds containing nitrogen-vacancy (NV) color centers play an important role in nanoscale sensing for their unique properties, including extraordinary photon stability, bio-compatibility, and chemical inertness at room temperature. Two-photon fluorescence imaging of fluorescent nanodiamonds (FNDs) has been studied with a picosecond pulsed laser operating at 1032 nm. We obtained an imaging resolution of 318 nm at nearly a third of the excitation wavelength with 70 nm FNDs. In this case, the resolution was improved by 2.2-fold, compared with the diffraction-limited resolution of the near-infrared (NIR) single-photon confocal microscopic imaging. The axial resolution of the imaging is about 750 nm, which is about 1.4 times higher than the Rayleigh length under the same excitation. The fluorescence spectra of visible and near-infrared excitation of FNDs are similar, suggesting that the energy levels involved in the two processes are identical. With the unique advantages of high spatial resolution, high signal-to-noise ratio (SNR), and infrared window matching, the study of two-photon excitation microscope imaging of FNDs is conducive to its broader application in biology, physics, and materials sciences.